Pengaruh Konten Instagram terhadap Minat Menonton: Studi Kasus Film 'Mencuri Raden Saleh' - Yeremia, Michael; Dharta, Firdaus Yuni; Ramdhani, Muhamad (CV. ITTC INDONESIA, 2024)
This research is motivated by the high number of social media users from year to year which also coincides with the birth of very popular social media platforms such as Facebook, Twitter, Youtube, Tiktok, Instagram. These social media platforms come with their own sophistication and advantages. Social media users can share anything with other users around the world in the form of text, video, sound or images. In Indonesia itself, Instagram is the most popular social media. Based on the We Are Social report, the number of global Instagram users reached 1.63 billion as of April 2023, which shows an increase of 12.2% compared to the previous year. The popularity of Instagram is certainly not wasted by film industry companies in Indonesia. Instagram @mencuriradensalehfilm is a social media account for a film produced by Visinema Pictures and directed by Angga Dwimas Sasongko entitled Mencuri Raden Saleh. Mencuri Raden Saleh is the first Indonesian film in the theft genre. The film Mencuri Raden Saleh is more active in promoting on Instagram @mencuriradensalehfilm because it can take advantage of Instagram's features. This film also managed to enter the 10 best-selling Indonesian films in 2022. Therefore, this research was conducted to find out how much influence Instagram content @mencuriradensalehfilm has on interest in watching the film Mencuri Raden Saleh. This research uses the AIDA Theory (Attention, Interest, Desire, Action) to see whether Instagram content can generate interest in watching the film Mencuri Raden Saleh. The research method used is quantitative, with the sample selection used being Non-Probability Sampling, namely a sampling technique that does not provide a chance for each selected population to become a sample. (Instgram followers @mencuriradensalehfilm). This research uses data analysis including descriptive analysis, normality test, simple linear regression test, coefficient of determination, and t hypothesis test. Based on the test results, the promotional variable Mencuri Raden Saleh Film on the Instagram account @mencuriradensalehfilm or variable X has a positive influence of 35.6% on variable Y and the remaining 64.4% is influenced by other factors.